Property and Function of a Novel Chitinase Containing Dual Catalytic Domains Capable of Converting Chitin Into N-Acetyl-D-Glucosamine - Wang, Chengyong; Chen, Xueman; Zhou, Ning; Chen, Yan; Zhang, Alei; Chen, Kequan; Ouyang, Pingkai (Frontiers in Microbiology, 2022)
A novel chitinase (CmChi3) encoding gene was cloned from Chitinolyticbacter meiyuanensis and actively expressed in Escherichia coli. Sequence analysis showed that CmChi3 contains two glycoside hydrolase family 18 (GH18) catalytic domains, and exhibited low identity with well-characterized chitinases. The optimum pH and temperature of purified recombinant CmChi3 were 6.0 and 50℃, respectively. CmChi3 exhibited strict substrate specificity of 4.1 U/mg toward colloidal chitin (CC) and hydrolyzed it to yield N-acetyl-D-glucosamine (GlcNAc) as the sole end product. Analysis of the hydrolysis products toward N-acetyl chitooligosaccharides (N-acetyl COSs) and CC substrates revealed that CmChi3 exhibits endochitinase, N-acetyl-β-d-glucosaminidase (NAGase), and transglycosylase (TGase) activities. Further studies revealed that the N-terminal catalytic domain of CmChi3 exhibited endo-acting and NAGase activities, while the C-terminal catalytic domain showed exo-acting and TGase activities. The hydrolytic properties and favorable environmental adaptations indicate that CmChi3 holds potential for commercial GlcNAc production from chitin.